The Behavior Accounting As A History : Perspective Single And Double Entry Bookkeeping - Yandari, Aprilya Dwi; Rofik, Mohammad (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2019)
At this writing has the purpose of how accounting behavior viewed in terms of history if there is accounting treatment with the perspective of single and double entry bookkeeping. The type of research carried out in the study is descriptive, by describing the results of sources obtained from secondary data and documentation data collection techniques such as, articles, journals, books, and others. The results obtained were analyzed based on the accounting aspects of the behavior of accounting records and accounting processes using single and double entry bookkeeping. Based on the historical perspective, the use of single and double entry bookkeeping is an ethic in psychology that exists in human rights where individuals have a value of rights that is naturally a form of their existence as humans. One of them in accounting is the right of accounting behavior to find out information related within the scope of a company, government, or other organization. While the behavioral approach is based on positive ethics, where with ethical behavior can see a state of actual habits that govern people's behavior. Keywords : history, single entry bookkeeping, double entry bookkeeping